Birth rites and name giving amond the Azza of Manga (Republic of Niger) - (:unkn) unknown (My University, 1974)
This article describes the birth rites and rules of name giving among the Azza of eastern Niger, as observed in 1969. The Azza, 'blacksmiths' of the Tubu (Chad, Niger), have been emancipated since colonisation and breed cattle and goats. Birth rites have both male Islamic and female pre-Islamic aspects. A visiting "marabout", who has come from Nigeria to recruit pupils for his Koranic school and receive donations of animals, lectures the audience on the rigour of the ritual to be observed, which makes it possible to measure the level of Islamisation of the local population.
Keywords: African Research